Pengaruh Pembelajaran Jarak Jauh di Tengah Pandemi COVID-19 dan Kecemasan Orang Tua terhadap Perilaku Religius Siswa - Dyah Surti Murdiningsih; Mulyoto (Fahima, 2022)
The aims of this study were to 1) determine the effect of distance learning during the Covid-19 pandemic on the students’ religious behavior; 2) determine the effect of parental anxiety on the students’ religious behavior, 3) Knowing the effect of distance learning during the Covid-19 pandemic and parental anxiety about the students’ religious behavior of Muhammadiyah 1 Kartasura Junior High School academic year 2020/2021. This research is quantitative. The sample of this study was 72 students of Muhammadiyah 1 Kartasura Junior High School academic year 2020/2021. Test the instrument using validity and reliability tests. Classical assumption test using normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used Multiple Linear Regression, F test, t-test, and coefficient of determination (R2). The results showed that distance learning during the Covid-19 pandemic on the religious behavior of Muhammadiyah 1 Kartasura Junior High School students academic year 2020/2021 proved to have a negative effect. The effect of parental anxiety on the religious behavior of Muhammadiyah 1 Kartasura Junior High School students academic year 2020/2021 has been proven to impact positively. The impact of distance learning during the Covid-19 pandemic and parental anxiety on the religious behavior of Muhammadiyah 1 Kartasura Junior High School students academic year 2020/2021 has proven to be influential.